2020
DOI: 10.1063/1.5128502
|View full text |Cite
|
Sign up to set email alerts
|

Physical chemistry of the TiN/Hf0.5Zr0.5O2 interface

Abstract: Ferroelectric hafnia-based thin films are promising candidates for emerging high-density embedded nonvolatile memory technologies, thanks to their compatibility with silicon technology and the possibility of 3D integration. The electrode–ferroelectric interface and the crystallization annealing temperature may play an important role in such memory cells. The top interface in a TiN/Hf0.5Zr0.5O2/TiN metal–ferroelectric–metal stack annealed at different temperatures was investigated with X-ray photoelectron spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 41 publications
8
101
0
Order By: Relevance
“…Furthermore, it can be described by two current peaks popping up at either direction of the current-voltage (I-V ) curve that might even merge to a single peak then resembling the standard distribution of coercive fields (E C ), as shown in Figure 1b. This behavior has been reported already by multiple groups [6,18,22,26,29,[31][32][33][34] and will be referenced to as the classical wake-up effect.…”
Section: Differences In the Wake-up Behavior Of Hafnium Oxidesupporting
confidence: 65%
“…Furthermore, it can be described by two current peaks popping up at either direction of the current-voltage (I-V ) curve that might even merge to a single peak then resembling the standard distribution of coercive fields (E C ), as shown in Figure 1b. This behavior has been reported already by multiple groups [6,18,22,26,29,[31][32][33][34] and will be referenced to as the classical wake-up effect.…”
Section: Differences In the Wake-up Behavior Of Hafnium Oxidesupporting
confidence: 65%
“…In summary, La doping of Hf 0.5 Zr 0.5 O 2 results into a stronger stabilization of the nonpolar tetragonal phase [ 6,31 ] by introducing oxygen vacancies [ 32 ] in the La‐doped regions (see green layers in the middle of the Hf 0.5 Zr 0.5 O 2 layer in Figure ). The creation of oxygen vacancies at metal/ferroelectric interface due to an oxygen scavenging effect of TiN is also reported in the literature; [ 32–34 ] therefore, a formation of nonpolar tetragonal phase at metal/ferroelectric interface [ 16 ] is also included into figure (see additional green layers at the ferroelectric/metal interface in Figure 5). The field‐cycling at 380 K can result in injection of charges into nonpolar dielectric layer at the metal/ferroelectric interface and into a minor tetragonal to orthorhombic phase change (Figure 5B).…”
Section: Resultsmentioning
confidence: 87%
“…Recent HAXPES measurements by Szyjka et al 83 also indicated a different oxidation state at the interfaces with the top and the bottom electrode, respectively. Hamouda et al 41,84 measured that the difference in electrode oxidation is accompanied by a V O gradient within the oxide from 0.7 to 0% as a function of probing depth when moving from top to bottom electrode (Fig. 11).…”
Section: Fecap Materials Stackmentioning
confidence: 99%